WUSCHEL-D1 upregulation enhances grain number by inducing formation of multiovary-producing florets in wheat - Adam Schoen; Guilherme V. Yoshikawa; Parva Kumar Sharma; Alex Mahlandt; Yi Chen; Huajin Sheng; Leon Kochian; Peng Gao; Daoquan Xiang; Teagen D. Quilichini; Prakash Venglat; Sheng Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
Innovative genetic improvements in food crops are needed to maintain global food security. Here, we report the map-based cloning of TaWUSCHEL-D1 ( WUS-D1 ) as the gene responsible for the multiovary phenotype in wheat, which produces three fertile ovaries and grains per floret. We generated a 14.5 Gbp chromosome-level assembly of multiovary wheat line “MOV” that shows unique structural variation in the Mov-1 physical region, resulting in widespread gene upregulation. High-resolution genetic mapping refined the locus to a 135 kbp region that contains two genes. We used nine independent deletion mutants, eight TILLING mutants, and genetic complementation of these genotypes to show that a WUSCHEL ortholog, WUS-D1 , is the causal gene of the Mov-1 locus. Expression studies showed that WUS-D1 is highly expressed during early inflorescence development in MOV, whereas the gene is inactive in wild-type wheat. The higher WUS-D1 expression is associated with the formation of larger meristems and floret primordia that are competent to produce multiple ovaries. These insights provide a foundation to manipulate floral organ numbers to enhance breeding capabilities of bread wheat.